Analisis Puisi “ Sejadah Panjang” Karya Taufiq Ismail Dengan Menggunakan Pendekatan Mimetik - Cindy Agustin; Munaris Munaris; Heru Prasetyo (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This mimetic approach assumes that poetry is a duplicate of the human world and a picture of the life of the universe. The extent to which poetry represents writers in the real world is explored alongside works of fiction or non-fiction and other works. Literature is dialectical, that is, it gives a journey back and forth to literary works and gives meaning in the end to the world of reality or imagination. The reality of an essential literary work will lose something when it is published, the disappointed participation in reading literature denies something that is no less important, namely for humans there are choices and shortcomings that exist.